Acute airway inflammation following controlled biodiesel exhaust exposure in healthy subjects - Thomas Sandström; Jenny A. Bosson; Ala Muala; Mikael Kabéle; Jamshid Pourazar; Christoffer Boman; Gregory Rankin; Ian S. Mudway; Anders Blomberg; Maria Friberg (Particle and Fibre Toxicology)
Abstract Background Exposure to standard petrodiesel exhaust is linked to adverse health effects. Moreover, there is a mounting request to replace fossil-based fuels with renewable and sustainable alternatives and, therefore, rapeseed methyl ester (RME) and other biofuels have been introduced. However, recent toxicological research has indicated that biodiesel exhaust may also induce adverse health-related events. Aim To determine whether exposure to 100% RME biodiesel (BD100) exhaust would cause an acute airway neutrophilic recruitment in humans. Methods Fourteen healthy subjects underwent exposure to diluted BD100 exhaust and filtered air for 1-h, in a blinded, random fashion. Bronchoscopy with endobronchial mucosal biopsies, bronchial wash (BW) and bronchoalveolar lavage (BAL) was performed six hours after exposure. Differential cell counts and inflammatory markers were determined in the supernatant and biopsies were stained immunohistochemically. Results Compared with filtered air, BD100 exhaust exposure increased bronchial mucosal endothelial P-selectin adhesion molecule expression, as well as neutrophil, mast cell and CD68 + macrophage numbers. An increased influx of neutrophils and machrophages was also seen in BW. Conclusion Exposure to biodiesel exhaust was associated with an acute airway inflammation that appeared similar to preceding petrodiesel exposure studies. The present findings, together with the recently reported adverse cardiovascular effects after similar biodiesel exposure, indicate that biodiesel is not free of toxicity and may affect human health.